Variabilidade genética da tolerância à salinidade causada por sulfato de amônio em milho (Zea mays L), variedade "Piranão" - Peters , Ingrid; Silva , José Carlos; Domingos Galvão , José (Revista Ceres, 2025)
The kinds of gene action conditioning the genetic tolerance of the maize variety “Piranão" to the salinity due to ammonium sulphate in the soil were studied. Additive and dominance genetic variances were estimated by utilizing Design I, proposed by COMSTOCK and ROBINSON, in 1952.